Systematic review of the methodological and reporting quality of case series in surgery. Issue 10 (11th August 2016) - Agha, R. A.; Fowler, A. J.; Lee, S.‐Y.; Gundogan, B.; Whitehurst, K.; Sagoo, H. K.; Jeong, K. J. L.; Altman, D. G.; Orgill, D. P.
Abstract : Background: Case series are an important and common study type. No guideline exists for reporting case series and there is evidence of key data being missed from such reports. The first step in the process of developing a methodologically sound reporting guideline is a systematic review of literature relevant to the reporting deficiencies of case series. Methods: A systematic review of methodological and reporting quality in surgical case series was performed. The electronic search strategy was developed by an information specialist and included MEDLINE, Embase, Cochrane Methods Register, Science Citation Index and Conference Proceedings Citation index, from the start of indexing to 5 November 2014. Independent screening, eligibility assessments and data extraction were performed. Included articles were then analysed for five areas of deficiency: failure to use standardized definitions, missing or selective data (including the omission of whole cases or important variables), transparency or incomplete reporting, whether alternative study designs were considered, and other issues. Results: Database searching identified 2205 records. Through the process of screening and eligibility assessments, 92 articles met inclusion criteria. Frequencies of methodological and reporting issues identified were: failure to use standardized definitions (57 per cent), missing or selective data (66 per cent), transparency or incomplete reporting (70 per cent), whether alternative study designs were considered (11 per cent) and other issues (52 per cent). Conclusion: The methodological and reporting quality of surgical case series needs improvement. The data indicate that evidence‐based guidelines for the conduct and reporting of case series may be useful. Abstract : Guidelines are needed